2015
DOI: 10.3390/w7116117
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Time-Scale Monitoring to Address Dynamic Seasonality and Storm Pulses of Stream Water Quality in Mountainous Watersheds

Abstract: Rainfall variability and extreme events can amplify the seasonality and storm pulses of stream water chemistry in mountainous watersheds under monsoon climates. To establish a monitoring program optimized for identifying potential risks to stream water quality arising from rainfall variability and extremes, we examined water chemistry data collected on different timescales. At a small forested watershed, bi-weekly sampling lasted over two years, in comparison to three other biweekly sampling sites. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The turbidity of river water may vary seasonally and spatially. For example, a heavy storm can result in more turbid river water due to the production of cohesive sediments from land disturbance and soil runoff [1,2]. In contrast, biota-rich rivers tend to be less turbid because biota have the ability to trap cohesive sediments through flocculation, sedimentation, and filtration [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The turbidity of river water may vary seasonally and spatially. For example, a heavy storm can result in more turbid river water due to the production of cohesive sediments from land disturbance and soil runoff [1,2]. In contrast, biota-rich rivers tend to be less turbid because biota have the ability to trap cohesive sediments through flocculation, sedimentation, and filtration [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The DO of the stream water was highly variable (CV = 1.81) ranging between 7.3 and 14.5 mg/L (mean = 10.9 mg/L) with a strong negative correlation with the water temperature (r = -0.905, p < 0.0001). The DO was at a seasonal low in summer, while it was at a seasonal high in winter because the oxygen solubility decreased with the increasing water temperature (Lee et al, 2015;Dick et al, 2016). Based only on the dissolved oxygen, the stream water was under very good conditions, irrespective of the turbidities.…”
Section: Resultsmentioning
confidence: 99%
“…6a). Coniferous forest composed of red pine, nut pine, and white birch trees accounts for ~26%, deciduous forest (oak, royal azalea, and dwarf small-leaf birch trees) account for 29%, and the remainder is mixed forest (Lee et al, 2015). The paddy field area did not significantly change during that period, but a slight decrease has been recorded recently due to the expansion of roads and buildings.…”
Section: Land Use and Land Cover Change Of The Basinmentioning
confidence: 96%
“…The rainfall events resulted in the dilution of solute concentrations. Similarly, Lee et al (2015) found a response from solutes in the Haean Basin, between South Korea and North Korea, whereby dilution of stream ions varied relative to rainfall intensity, duration and antecedent moisture conditions. Furthermore, the uniform response of most solutes at different sites over the time series, in particular Na + and Cl − , indicates that variation in solute concentrations is predominantly controlled by rainfall inputs (Neal et al 2012).…”
Section: Temporal and Spatial Variabilitymentioning
confidence: 89%